Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Dan Disiplin Kerja Terhadap Kinerja Di Dinas Pendidikan Kabupaten Tulungagung - Darmono, Darmono; Mulyaningtiyas, Ratna Dewi (Universitas Islam Kadiri, 2024)
This research aims to: Analyzing the simultaneous significant influence of Transformational leadership, motivation, and work dicipline on employee performance ;analyzing the influence of transformational Leadershipstyle on employee performance ; analyzing the influence of Motivationon employee performance ; analyzing the influence of work Disipline on employee performance. This research uses Descriptive Quantitative. the population in this research is in the Tulungagung district education office. The researcher does not specify a sample, because all members of the population will be examined. The technique is a method of data collection now. In this study, researchers used the software (software), Microsoft Office Excel 2007 to carry out a descriptive and statistical analysis software (software) Statistical Package for Social Sciences (SPSS) for Windows version 21.0 to carry out the test, test the classical, hypothesis testing and multiple linear regression analysis, , The research findings indicate a significant influence betwen the variables of Transformational leadership, motivation, and work discipline on employee performance in the Tulungagung district education office. meanwhile the most dominant influencingvariable is the Motivation